An approximate matching method for a parallel sequential turbocharging system. (July 2015) - Qian, Yuehua; Li, Hualei; Deng, Kangyao
A theoretical study on matching a parallel sequential turbocharging system and a diesel engine is conducted. The relationship between the turbocharging system and the engine is represented through expressions for the geometry-equivalent areas of the turbine nozzle and the engine parameters, which are derived on the basis of the thermodynamics equations, and the mass and energy conservation of the turbocharging engine system. The feasible range of the geometry-equivalent areas of the turbine nozzle for a given engine operation condition is determined by the limits of the engine and the turbochargers. The number of sequential turbocharging system phases is determined by the feasible range of geometry-equivalent areas of the turbine nozzle, and the switching boundaries are calculated for the engine's best performance. The matching method is applied to design the sequential turbocharging system for a six-cylinder diesel engine. The results prove that the number of phases and the switching boundary are accurately estimated by this model. The relative error in the pressure ratio between the results obtained by this matching method and those determined by the validated GT-Power model is less than 6.4%. It is helpful for sequential turbocharging preliminary selection and for providing a foundation for a further matching method.